Peningkatan Kemampuan Menulis Teks Laporan Hasil Observasi dengan Menggunakan Metode Pemodelan pada Siswa MTs Negeri 4 Bantul - Purwanto (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
The study aims to improve the ability to write the text of the observation report using modeling methods. This research was conducted in the students of the VII-A Madrasah Tsanawiyah Negeri 4, the semester of the year, 2019/2020. This research uses class action methods. Data collection techniques using tests and validity of data are obtained through the validity of the process and the validity of results. The results showed that: (1) Learning to write the text of an observation report using modeling methods can improve the student's ability to write the text of the observation report. This is seen from the average value of the ability to write the text of an observation report before the action is 56.04, increasing to 61.7 on cycles 1 and 77.96 on cycle II. Increased average score from pre-action to cycle I, amounting to 4.90, and to cycle II by 12.67. Increased total average score from pre-action to cycle II by 17.57. (2) The enhancement of the learning process using modeling methods can be seen from the enthusiasm, attention, and activity of students so as to improve the quality of learning to write the report of the observation result and positive change for students. Therefore, the use of modeling methods in learning to write the text of an observation report can be more interesting and enjoyable.